POTT’S Disease - Tutik Kusmiati; Hapsari Paramita Narendrani (Jurnal Respirasi, 2016)
Pott's disease, sometimes reffered to tuberculous spondylitis, is an infection of tuberculosis that affects one or more vertebrae, which first described by Percival Pott. Tuberculous spondylitis is the most dangerous form of musculoskeletal tuberculosis because it can cause bone destruction, deformity and paraplegia. The spine is the most commonly affected due to bony dissemination of tuberculosis in bones. The deployment through the arteries, veins via Batson plexus and percontinuitatum by the spread of abscess paravertebral. The spread of tuberculosis infection will cause inflammation in paradiscs, and causes progressive bone destruction and then will make vertebral collapse and deformity arising shaped kyphosis (posterior angulation) called gibbus. Early diagnosis is often difficult, MRI is the best diagnostic tools for pott's disease. Tissue culture or spesimen of M. tuberculosis important to confirm the diagnosis. Medical treatment is preferred, whereas surgical therapy as a complements. Drop out of anti-tuberculous drugs is a major challenge for the treatment of spinal TB with MDR because of long duration of therapy and the cost. The prognosis for spinal TB increases with early diagnosis and rapid intervention.